(untitled) - Werner Burkhardt (New York, 1994)
Maple is a computer algebraic system with a fast-growing number of users in universities, schools and other institutions. It provides a detailed step-by-step introduction for all first-time users, enabling to become familiar with the way Maple works, as quickly and easily as possible. Using as examples problems from many different aspects of mathematics, problem solving using Maple is fully described in this easy-to-follow tutorial text. Each chapter is self-contained. There are some 'test yourself' problems at the end of each chapter to check your progress, with solutions provided at the end of the book
Keywords: computer science - mathematics,maple ( computer programs )